Preoperative breast volume evaluation of one-stage immediate breast reconstruction using three-dimensional surface imaging and a printed mold. Issue 9 (September 2019) - Chen, Keng; Feng, Chin-Jung; Ma, Hsu; Hsiao, Fu-Yin; Tseng, Ling-Ming; Tsai, Yi-Fang; Lin, Yen-Shu; Huang, Li-Ying; Yu, Wen-Chan; Perng, Cherng-Kang
Abstract : Background: Accurate assessment of breast volume is an essential component of preoperative planning in one-stage immediate breast reconstruction (IBR) for achieving breast symmetry and a satisfactory cosmetic outcome. In this study, we compared breast volume estimation using three-dimensional (3D) surface imaging with magnetic resonance imaging (MRI) to determine the accuracy of breast volume measurements. Further, a 3D printing mold for facilitating autologous breast reconstruction intraoperatively is described. Methods: Patients scheduled to therapeutic or prophylactic mastectomy with one-stage IBR, either by autologous tissue transfer or direct implant, from 2016 to 2019, were enrolled in this study. 3D surface image and MRI were performed to evaluate breast volume and shape. The results were validated by the water displacement volume of the mastectomy specimen. Finally, a 3D printing mold was designed for breast reconstruction with autologous tissue. Results: Nineteen women who were scheduled to have 20 mastectomies (18 unilateral and one bilateral) were included. There was a strong linear association between breast volume measured using the two different methods and water displacement of mastectomy specimens when a Pearson correlation was used (3D surface image: r = 0.925, p < 0.001; MRI: r = 0.915, p < 0.001). Bland-Altman plots demonstrated no proportional bias between the assessment methods. The coefficient of variation was 52.7% for 3D surface imaging and 59.9% for MRI. The volume of six breasts was evaluated by both measurements and the intraclass correlation coefficient was 0.689 for 3D surface image ( p = 0.043) and 0.743 for MRI ( p = 0.028). Conclusion: Using 3D surface image to evaluate breast shape and volume is a quick, effective, and convenient method. The accuracy, reproducibility, and reliability of 3D surface imaging were comparable with MRI in our study. In addition, 3D-printed molds can achieve better symmetry and aesthetic outcomes in immediate autologous breast reconstructions.